THE ROLE OF INTERNAL CONTROL TECHNIQUES IN SUSTAINABLE DEVELOPMENT FOR IMPROVING ACCOUNTING DISCLOSURE - Hayder Basim Kareem (Scholar Express Journals, 2025)
This research pursuits to have a look at the effect of applying current internal control techniques in assisting the targets of sustainable development and enhancing the level of accounting disclosure in monetary institutions. With the speedy development of work environments and the increasing needs for transparency and accountability, internal manage has become a strategic tool that not handiest contributes to asset safety and achieving operational efficiency however additionally ensures the supply of correct and dependable accounting facts that aids in making rational and sustainable selections. The studies first addresses the theoretical framework of both inner manage and sustainable development standards, with a focal point on their interactive courting. It then critiques more than a few modern-day organizational strategies, which include the use of automated accounting facts systems, hazard analysis gear, and continuous evaluation methods, highlighting how these tools make contributions to improving the excellent of accounting records
Keywords: internal manage; evaluation; highlighting